GERAKAN KEAGAMAAN TAREKAT NAQSABANDIYAH BABUL KAROMAH DI LABUHAN BATU UTARA - Pasaribu, Juwinda; Riza, Faisal (FISIP Universitas Malikussaleh, 2025)
This research examines the Naqsyabandiyah Babul Karomah Tarekat religious movement in Bandar Durian Village, North Labuhan Batu. This congregation is a form of Sufism practice which plays an important role in shaping the socio-religious behavior of local communities. The research method used is qualitative with observation, interview and documentation techniques. The focus of this study includes core teachings, such as dhikr, tawajjuh, and robithoh, as well as the dynamics of tarekat organizations in the region. The research results show that the practice of this congregation has a positive impact on the social and religious behavior of the congregation, creates personal and collective piety, and improves friendship and spiritual quality. In addition, this tarekat shows the ability to adapt in facing modernization, even though it faces challenges in maintaining its followers in the era of globalization. This research makes an important contribution to understanding the role of congregations in modern society, especially in efforts to preserve religious traditions amidst social change.